North Africa 2030 What the Future Holds for the Region - Mezran, Karim (ISPI Publications, 2021)
Over ten years after the "Arab Spring", the turmoil that swept across North Africa has taken many forms, bringing about change, although not always in a desirable direction. But the Arab uprisings have also brought about a surprising amount of "more of the same": a decade on, the problems that plagued the region in 2010 have not gone away. This report looks at the future of the region, asking: what will North Africa be in 2030? Which direction could the region as a whole, and specific countries, take, and which challenges will they have to face? And what are the implications for Europe and the US?